2017
DOI: 10.1111/nin.12217
|View full text |Cite
|
Sign up to set email alerts
|

Influencing everyday activities in a nursing home setting: A call for ethical and responsive engagement

Abstract: This study focuses on influence that older adults, living in nursing homes, have over everyday activities. Everyday activities are key to sustain a sense of stability, predictability, and enjoyment in the local world of people's everyday and therefore a critical dimension of the person‐centeredness framework applied within gerontology. This narrative ethnographic study aimed to shed light on how influence can be situated contextually, and how it can emerge through activities as well as how it is negotiated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 71 publications
(141 reference statements)
3
46
0
2
Order By: Relevance
“…Nevertheless, this is not consistent with the fact that the majority of the nursing staff said that residents were offered the opportunity to be involved in individualized everyday activities as reported in one of the items in the P-CAT questionnaire. A possible explanation [41], who suggested that the deeper meaning of everyday activities might remain invisible to the staff representing and focusing on the institutional routines, or as Smebye and Kirkevold [42] indicated in their study: the activities were not self-evident in the context of nursing homes. Workload or the high prevalence of residents with cognitive impairment in nursing homes have also been suggested as possible explanations for the lack of provision of activities [43].…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, this is not consistent with the fact that the majority of the nursing staff said that residents were offered the opportunity to be involved in individualized everyday activities as reported in one of the items in the P-CAT questionnaire. A possible explanation [41], who suggested that the deeper meaning of everyday activities might remain invisible to the staff representing and focusing on the institutional routines, or as Smebye and Kirkevold [42] indicated in their study: the activities were not self-evident in the context of nursing homes. Workload or the high prevalence of residents with cognitive impairment in nursing homes have also been suggested as possible explanations for the lack of provision of activities [43].…”
Section: Discussionmentioning
confidence: 93%
“…In a previous study conducted in the same setting [24] occupational interests among older adults living at a NH and the facilitating conditions to enact those interests were explored. The main findings revealed that older adults wanted to feel connected with the world outside the NH, to put their capabilities in action, to have something to look forward to, to have a chance of meeting new people and to feel active in their own capacity.…”
Section: Project Design: the Creation Of A Third Spacementioning
confidence: 99%
“…Older adults' engagement in occupations is an important issue in the development of quality standards and the person-centred approach [1][2][3] within nursing home (NH) and has been a clear focus in aging research [4][5][6][7][8], occupational therapy research [9][10][11][12][13][14][15][16], policy [17][18][19] and in clinical practices. It is well known that older adults' engagement in occupations contributes positively to quality of life and meaning making [13,[20][21][22][23][24][25]. Although an occupational perspective [26] is often an important part of NH settings, many programs fail to incorporate and accommodate the residents' views and resources [2,11,14,24,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations